Niche-Neutral Continuum Seems to Explain the Global Niche Differentiation and Local Drift of the Human Digestive Tract Microbiome - Chen, Hongju (Daisy); Ma, Zhanshan (Sam) (Frontiers in Microbiology, 2022)
The human digestive tract (DT) is differentiated into diverse niches and harbors the greatest microbiome diversity of our bodies. Segata et al. (2012) discovered that the microbiome of diverse habitats along the DT could be distinguished as four types; each is different not only in community composition, but also in metabolic potentials. Nonetheless, few studies have offered theoretical interpretations of the observed patterns, not to mention quantitative mechanistic parameters. Such parameters should capture the essences of the fundamental processes that shape the microbiome distribution, beyond simple ecological metrics such as diversity or composition descriptors, which only capture the manifestations of the mechanisms. Here we aim to get educated guesses for such parameters by adopting an integrated approach with multisite neutral (MSN) and niche-neutral hybrid (NNH) modeling, further augmented with species-level Sloan’s near neutral model, via reanalyzing Segata’s 16s-rRNA samples covering 10 DT-sites from over 200 healthy individuals. We evaluate the relative importance of the four essential processes (drift, dispersal, speciation, and selection) in shaping the microbiome distribution and dynamics along DT, which leads to a niche-neutral continuum. Furthermore, the continuum is hierarchical: the selection or niche differentiations seem to play a predominant role (>90% based on NNH) at the global (the DT metacommunity) level, but the neutral drifts seem to be prevalent (>90% based on MSN/NNH) at the local sites except for the gut site. The species-level neutrality analysis further suggested that the gut is inhabited by significantly high proportion of positively selected bacterial species than other DT sites, possibly attributed to selection effects of fully digested food. An additional finding is that the DT is differentiated into five niches and a new fifth niche “Keratinized gingival (KG)” exists.